Grotesque elements in two selected short stories - Haghighi, Hana; Talif, Rosli (Universiti Putra Malaysia Press, 2014)
This study aims to identify and analyse grotesque elements in two selected short stories: The Judge’s House by Bram Stoker (1847–1912), an Irish writer, and The Cursed Citadel by an Iranian writer, Sadegh Hedayat (1903-1951). Pertaining to two different cultures with different backgrounds, the selected stories include several grotesque elements in both their structures and subject matters. The grotesque elements in the selected short stories are manifested through literary devices including characters, plots, atmosphere, and style. The characters of both stories are depicted as irregular as well as extravagant creatures and the plots are teemed with strangeness and abnormalcy representing distorted reflection of known familiar places and parodies of human qualities. These elements disable the characters and provide a fragmented and alienated perception of the world. Retaining the features of the grotesque genre along with attempting to symbolize the ugly reality through illustrating atrocity and cruelty in the world, both authors take familiar ordinary things and deform them in both content and form. As a result, there is an element of truth in images, situations, characters, and events despite their entirely exaggerated representation.